A new species of the genus Johanssonia Selensky, 1914 (Hirudinea: Piscicolidae) collected in the Kuril-Kamchatka Trench at the greatest depth ever recorded for fish leeches. (September 2019) - Utevsky, Serge; Kovalchuk, Anastasiia; Kovalchuk, Nataliia; Utevsky, Andriy; Chernyshev, Alexei V.
Highlights: Johanssonia extrema n. sp. lives at the greatest depth ever recorded for leeches. A possible fish host of J. extrema n. sp. is the Pacific grenadier. Johanssonia extrema  n. sp. is sister to the boreal-arctic fish leech  J. arctica . The new leech lacks uncommon external organs for adaptation to deep-sea life. Fish leeches play an important role in deep-sea benthic communities. Abstract: Johanssonia extrema n. sp. was described from a depth of 8728.8 m in the Kuril-Kamchatka Trench. The leech is elongate, up to 58 mm total length. Body is smooth, lacking papillae, tubercles, pigmentation, eyes and ocelli. Suckers are well-developed, eccentrically attached. Lateral pulsatile vesicles are present. Posterior crop caeca are fused. The male reproductive system is characterised by six pairs of testisacs, elongate, tubular atrial cornua and ejaculatory ducts, and coiled seminal reservoirs. The female reproductive system has ovisacs with oviducts looping back anteriorly and a well-developed conductive tissue mass. A possible fish host is the Pacific grenadier Coryphaenoides acrolepis (T. H. Bean, 1884). The molecular phylogenetic analysis revealed sister relationships between the new species and the boreal-arctic fish leech Johanssonia arctica (Johansson, 1898).